2020
DOI: 10.2174/1381612826666200131100630
|View full text |Cite
|
Sign up to set email alerts
|

Wnt/beta-catenin and PI3K/Akt/mTOR Signaling Pathways in Glioblastoma: Two Main Targets for Drug Design: A Review

Abstract: : Glioblastoma (GBM) is the most common and malignant astrocytic glioma, accounting for about 90% of all brain tumors with poor prognosis. Despite recent advances in understanding molecular mechanisms of oncogenesis and the improved neuroimaging technologies, surgery, and adjuvant treatments, the clinical prognosis of patients with GBM remains persistently unfavorable. The signaling pathways and the regulation of growth factors of glioblastoma cells are very abnormal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 73 publications
1
58
0
2
Order By: Relevance
“…The above results showed that PODNL1 could promote cell proliferation, migration and inhibit EMT in glioma cells. Currently, accumulating studies have reported that Akt/mTOR pathway directly regulates malignant behaviors in glioma [12,13]. Thus, we supposed that PODNL1 aggravated malignant behaviors through Akt/mTOR pathway in glioma cells.…”
Section: Podnl1 Promoted Cell Proliferation and Migration Via Akt/mtomentioning
confidence: 87%
“…The above results showed that PODNL1 could promote cell proliferation, migration and inhibit EMT in glioma cells. Currently, accumulating studies have reported that Akt/mTOR pathway directly regulates malignant behaviors in glioma [12,13]. Thus, we supposed that PODNL1 aggravated malignant behaviors through Akt/mTOR pathway in glioma cells.…”
Section: Podnl1 Promoted Cell Proliferation and Migration Via Akt/mtomentioning
confidence: 87%
“…Change in calcium signaling is a major modulator of the glial cell behavior [43]. -PI3K-Akt signaling (hereafter denoted by PA) is pivotal for the growth, metabolism, survival, angiogenesis, autophagy, and chemotherapy resistance of the malignant astrocytic glioma [44]. -Chemokine signaling (CS) between astrocytes and oligodendrocytes, most likely the main crosstalk in our experiment, is important for glial development and stimulating regeneration and repair [45].…”
Section: Pathway Analysismentioning
confidence: 93%
“…Furthermore, specific molecules within this signaling pathway have been untested at the epigenetic and transcriptional levels. A need for a better understanding of the function and mechanisms of PI3K-AKT-mTOR signal transduction may eventually provide advanced diagnostic and treatment options for primary brain neoplasms [ 9 , 18 ]. This study aims to understand the significance of the EGFR-PI3K-AKT-mTOR signaling pathway and reveal differences between AKT1 , AKT2 , AKT3 , CHUK , GSK3β , EGFR , PTEN , and PIK3AP1 roles within different grades and types of diffuse brain gliomas.…”
Section: Introductionmentioning
confidence: 99%